2011
DOI: 10.7202/045587ar
|View full text |Cite
|
Sign up to set email alerts
|

Career Satisfaction: A Look behind the Races

Abstract: Previous studies have largely focused on the career success of white employees (Heslin, 2005). Using recent survey data, this paper examines the career satisfaction levels of white/Caucasian and visible minority managerial, professional and executive employees in the information and communications technology [ICT] and financial services sectors in corporate Canada. Given that the demographic makeup of organizations in Canada is drastically changing with the aging population and the increasing participation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
(134 reference statements)
2
17
1
2
Order By: Relevance
“…The level of education and tenure were found to be significantly positively related to employees' career satisfaction, which contrasts with previous research findings (Seibert and Kraimer, 2001;Yap et al, 2010). Level of education and tenure were not related to job satisfaction in the present research.…”
Section: Discussioncontrasting
confidence: 57%
“…The level of education and tenure were found to be significantly positively related to employees' career satisfaction, which contrasts with previous research findings (Seibert and Kraimer, 2001;Yap et al, 2010). Level of education and tenure were not related to job satisfaction in the present research.…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, research has shown that it has consequences on several beneficial organizational outcomes such as job performance, employee commitment, occupational retention as well as organizational retention (e.g., Igbaria, 1991;Pachulicz, Schmitt and Kuljanin, 2008;Yap et al, 2010). Interestingly, in the context of an aging workforce, subjective career success has also been shown to influence older workers' intention to remain with their organization (Armstrong-Stassen and Ursel, 2009).…”
Section: Résumé De L'articlementioning
confidence: 99%
“…Furthermore, Pendakur and Pendakur (2007) found that men and women of Chinese backgrounds face a larger negative wage gap in higher level positions than in lower positions, yet perceive the lowest level of discrimination among visible minorities (Banerjee, 2011;Yap & Everett, 2011). Overall, Chinese Canadians employees are 8.2% less satisfied with their careers than white/Caucasian employees in large firms (Yap et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…The objective of this study was to bring forth Chinese Canadian perspectives of their career mobility into senior leadership roles and to examine the thematic variations in their conceptions within the group of everyday practices that might perpetuate inclusion or exclusion. In Canada, Chinese Canadians represent a significant and important talent base for organizations (Yap et al, 2010;Zong & Perry, 2011), and while they represent just one bicultural group within the organizational setting, other bicultural groups likely experience culturally distinct dynamics. The aforementioned studies reinforce that employees want to be more fully understood for their specific ethnic identities whereas, many Canadianbased studies tend to focus on broad-based studies that look at visible minorities (Catalyst Canada & Diversity Institute, 2007;Conference Board of Canada, 2005) or perhaps an Asian demographic.…”
Section: Research Approach and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation